Ecological Network and Ecosystem Services - Yakovlieva, Sofiya; Cherkez, Eren; Corbei, Raluca; Hodžić, Haris; Manjate, Ana Lodomilla; Schmitz, Serge; Nicola, Sanda (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
To address the growing challenges faced by near-future cities—such as floods, water shortages, and heat islands—urbanism and ways of dwelling must adapt. Currently, two main approaches are favoured: technological solutions and nature-based solutions. To adopt the second option, a good understanding of green infrastructure is essential. This research aims to analyse the ecological network of Maribor, with particular emphasis on ecological corridors. For this analysis, we investigated both the actual ecological network and people's perception of ecosystem services through spatial analysis using GIS tools and a survey. Most respondents expressed satisfaction with the availability and accessibility of green spaces. However, the maps indicate that, although Maribor is surrounded by many green areas, including several Natura 2000 sites, some central districts need improvement. It is recommended to establish green corridors in these areas to create both an ecological network and to enhance ecosystem services.